AN ANALYSIS OF SWEAR WORDS USED IN GOOD BOYS MOVIE BY GENE STUPNITSKY - Tamola, Mifta Sulistia; Hidayati Otoluwa, Moon; Mukhsin, Hasna Nurain (LPPM STISIPOL Mujahiddin, 2024)
Swear words are used to express emotions such as sadness, happiness, anger, confusion, disappointment, frustration, and others. This work was conceived with the aim of exploring swear words that fit the context of the movie Good Boys by Gene Stupnitsky. This research uses qualitative method by using sociolinguistic approach. To obtain the types of swear word and to find out the types of swearing, the researcher used data analysis techniques by Miles & Huberman (1994), namely, data reduction, data display, conclusion. As a result of this study it found that there four types of swear words by Andersson & Trudgill (1992) known as Expletives Swear Words, Abusive Swear Words, Humorous Swear Words, Auxiliary Swear Swear Words. The results of this study show that the types of swear words obtained in the movie Good Boys with a total of 80 data and the type of swear words most commonly found is Expletive Swear Word with 49 data obtained. In contrast, the least type obtained is Humorous Swear Word with 5 data